Unresolved issues should be addressed post by-election - New Sabah Times, English (KK) (New Sabah Times, 2015)
ROMPIN: Barisan Nasional (BN)should address all unresolved issues, especially concerning the Goods and Services Tax (GST), after the Rompin byeiection because those issues can give a longterm impact to the party, said political analysts.